Comparison of Energy Absorption of Aluminium-composite Tubes Subjected to Axial Loading - Abbas, T. (Institute of Physics Publishing, 2017)
In this paper, energy absorption capability and failure modes of partially wrapped aluminium tubes have been studied. These tubes are used in the front side of automobiles and aircraft applications. Filament winding technique was used for partial wrapping of these tubes. Partially wrapping on the external surface of aluminium tubes was done with glass fibers, and epoxy resin, which is a composite material. Various composite layers and fiber angles were used in partial wrapping, which includes 4, 6 and 8 composite layers of ± 55° fiber angle. These tubes were subjected to axial crushing using the universal testing machine, and testing speed was 5mm/min. Failure modes and energy absorption analysis were carried out after testing. The experimental results revealed that partially wrapped aluminium tubes are 3.81, 8.13 and 17.06 more efficient in energy absorption as compared to the tubes without wrapping. Furthermore, the effect of composite layers and failure modes has also been described. © Published under licence by IOP Publishing Ltd.